Ilizarov non-free bone plasty for extensive tibial defects - Borzunov, Dmitry Y. (Springer-Verlag, 2013)
PURPOSE: The purpose of this study was to present a retrospective comparative overview of the Ilizarov non-free bone plasty techniques of one-stage multilevel fragment lengthening and gradual tibilisation of the fibula used for extensive tibial defect management. METHODS: Extensive tibial defects in 83 patients were managed either by multilevel fragment lengthening (group I, n = 41, mean defect size 13.1 ± 0.9 cm) or gradual tibilisation of the fibula (group II, n = 42, mean defect size 12.5 ± 1.2 cm) using the Ilizarov apparatus. The initial findings, treatment protocols and outcomes of those patients treated within the period 1972–2011 were studied retrospectively by medical records and radiographs, and statistically assessed with Microsoft Excel and Attestat software. RESULTS: Group I had multilevel fragment lengthening over one stage that averaged 288.0 ± 14.4 days. The mean total period of gradual tibilisation of the fibula in group II was 316.0 ± 29.7 days. The patient’s age in the latter group had an effect on the completeness of leg-length equalisation. CONCLUSIONS: The techniques can be used to manage extensive tibial defects as all the defects bridged, leg-length discrepancy and deformity were corrected and patients were able to load their limbs.